Statistical issues in allocating funds by formula - Louis, Thomas A., 1944-; Jabine, Thomas B.; Pineau, Marisa Gerstein (National Academies Press, 2003)
The Panel on Formula Allocations was formed in January 2001 to expand the existing research into allocating government money according to statistical formulas. This final report is intended to be considered in terms of its 2001, and case studies and methodological studies in the September 2002 special issue of . It is not indexed. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).